OPTIMALISASI PERAN GURU PAI DALAM MENCEGAH RADIKALISME PADA PESERTA DIDIK MUSLIM DI KABUPATEN RAJA AMPAT - Loji, Abu Bakar; Nur , Indria; Abdillah , Fardan (Pascasarjana IAIN Sorong, 2023)
The objectives of this scientific research are: 1) To describe the efforts of Islamic Religious Education teachers in preventing radicalism among students at SMA Negeri 1 Raja Ampat Regency. 2) To describe optimizing the role of Islamic Religious Education teachers in preventing radicalism among students at SMA Negeri 1 Raja Ampat Regency. This research uses descriptive qualitative research located at SMA Negeri 1 Raja Ampat. This research approach is a guidance approach and a sociological approach. Data sources in this research include primary data sources and secondary data sources. Data collection methods are observation, interviews and documentation. Analysis of this research data through data reduction, data presentation and drawing conclusions. The results of the research show that: 1) Optimization has been carried out by Islamic Religious Education Teachers in preventing radicalism, namely: a) Islamic Religious Education Teachers optimize explanations about Islam rahmatan lil 'aalamiin, b) Islamic Religious Education Teachers optimize dialogue in Islamic Religious Education learning. c) Islamic Religious Education Teachers optimize the introduction and application of Multicultural education. 2) The role of Islamic Religious Education Teachers in preventing radicalism is: a) Islamic Religious Education Teachers as educators, b) Islamic Religious Education Teachers as teachers, and c) Islamic Religious Education Teachers as mentors.